Las angiospermas epífitas de Puebla - Miguel Vázquez, Mónica Isabel (Universidad Autónoma Metropolitana, 2014)
Epiphytes are plants that have developed diverse adaptations to live at least one stage of their life cycle on other plants (Phorophytes) without haustoria and they comprise between 9 to 10% of the global plant diversity. Whithin angiosperms, families of monocots with most epiphyte taxa are Orchidaceae, Bromeliaceae and Araceae, while to dicots are Piperaceae, Ericaceae and Melastomataceae; with respect to Pteridophytes, almost the 29% have the epphytic habit. Puebla state has an área of 34290 km², 217 municipalities and eight vegetation types, it has a high biodiversity, producof its complex biogeographic histoy and its high topographic and climatic heterogenity. Of the 19 biogeographic provinces in which Mexico has been divided, seven are present in the entity and it is estimated that a fifth of the angiosperms reported for the country are distributed here; however, lacks of a complete floristic inventory. The present study had as objetive to realiza the inventory of wild epiphyte angiosperm flora from Puebla state. To do this, we revised literatura related to the subject, we examined the specimens deposited in the following herbaria: AMO, ENCB, FCME, HUAP, MEXU, UAMIZ, and XAL, and we made several recollection trips to different zones of the state. Base don the obtained information, we report the presence of 18 families, 91 genera and 263 species of angiosperm epiphytes for the state. Of these. 65 genera and 196 species are monocots, while 26 and 69are dicots. The best represented families at the specific level are Orchidaceae (123), Bromeliaceae (56), and Piperaceae (29), while the most diverse genera are Tillandsia, Peperomia, and Epidendrum with 40, 29 y 15 taxa respectively. The vegetation type with highest percentage of epiphytes is the cloud forest (50%), followed by the Quercus forest (32%) and the tropical evergreen forest (21%). The main phorophytes genera were Quercus and Busera. The altitudinal interval in which we recorded the largest number of epiphytic species in between 1090 to 1700 m. The months in which we found the highest njmber of species in Bloom were april to july. The municipalities with greatest number of records and species are: Cuetzalan del Progreso with 138 and 59, Hueytamalco with 101 and 55 and Xicotepec with 92 y 51, respectively, while of 29 (13%) there is only one record and for 105 (48%) none. We report flor first time to the state 22 species, corresponding to the families Araceae (2), Bromeliaceae (7), Crassulaceae (1), Gesneriaceae (1), Orchidaceae (1), and Piperaceae (10). Of all the species reported in this study, 72 (27%) are endemic to Mexico, being Orchidaceae and Bromeliaceae the families with the greatest number, both with the greatest number, both with 31. Refering to included species in some category of protection, 16 are catalogued in the NOM-059-SEMARNAT-2010; two corresponding to Bromeliaceae, two to Cactaceae, and 12 to Orchidaceae. The results show that Puebla is a state with high diversity of epiphytes, however, it is also a región whose vegetation has been severely affected by anthropogenic activities, so is necessary to carry out studies to know more about its flora and provide tolos to preserve it.; Las epífitas son plantas que han desarrollado diferentes adaptaciones para vivir al menos una parte de su vida sobre de otras plantas (forófitos) sin generar haustorios y comprenden entre 9 y 10% de la diversidad vegetal mundial. Dentro de las angiospermas, las familias de monocotiledóneas con mayor número de taxa epífitos son Orchidaceae, Bromeliaceae y Araceae, mientras que entre las dicotiledóneas son las Piperaceae, Ericaceae y Melastomataceae; en cuanto a las Pteridofitas, casi 29% presenta este hábito. El estado de Puebla tiene una superficie de 34 290 km², municipios, ocho tipos de vegetación y posee una gran biodiversidad producto de su compleja historia biogeográficas y de su alta heterogeneidad topográfica y climática. De las 19 provincias biogeográficas en que se divide a México, siete se encuentran en la entidad y se calcula que en ella se distribuye la quinta parte de las angiospermas reportadas para el país; sin embargo, carece de un inventario florístico completo. El presente estudio tuvo por objetivo inventariar la flora de angiospermas epífitas silvestres del estado de Puebla. Para ello se revisó literatura relacionada con el tema, se examinó el material depositado en los herbarios AMO, ENCB, FCME, HUAP, MEXU, UAMIZ y XAL y se realizaron viajes de recolección a distintas zonas del estado. Con base en la información obtenida reportamos la presencia de 18 familias, 91 géneros y 263 especies de angiospermas epífitas. De las mismas, 65 géneros y 196 especies corresponden al grupo de las monocotiledóneas, mientras que 26 y 69 al de las dicotiledóneas. Las familias mejor representadas a nivel específico son Orchidaceae (123), Bromeliaceae (56) y Piperaceae (29), mientras que los géneros más diversos son Tillandsia, Peperomia y Epidendrum con 40, 29 y 15 taxa respectivamente. El tipo de vegetación con mayor porcentaje de epífitas es el bosque mesófilo de montaña (50%), seguido por el bosque de Quercus (32%) y el bosque tropical perennifolio (21%). Los principales géneros de forófitos fueron Quercus y Bursera. El intervalo altitudinal en el que se registró mayor número de especies epífitas va de lso 1090 a los 1700 m. los meses en los que se encontraron más especies en floración fueron de abril a julio. Los municipios con mayor número de recolecciones y de especies son: Cuetzalan del Progreso con 138 y 59, Hueytamalco con 101 y 55 Xicotepec con 92 y 51 respectivamente, mientras que de 29 (13%) solo se tiene registrada una colecta y de 105 (48%) ninguna. Se reportan por primera vez para el estado 22 especies, correspondientes a las familias Araceae (2), Bromeliaceae (7), Crassulaceae (1), Gesneriaceae (1), Orchidaceae (1) y Piperaceae (10). Del total de especies reportadas en este estudio, 72 (27%) son endémicas de México, siendo Orchidaceae y Bromeliaceae las familias con mayor número de éstas, ambas con 31. En lo que se refiere a las especies incluidas en alguna categoría de protección, 16 se encuentran catalogadas en la lista de protección NOM-059SEMARNAT-2010: dos corresponden a Bromeliaceae, dos a Cactaceae y 12 a Orchidaceae. Los resultados muestran que Puebla es un estado con alta diversidad de epífitas, sin embargo también es una región cuy vegetación ha sido gravemente afectada por las actividades antropogénicas, por lo que resulta urgente realizar estudios que permitan conocer más acerca de su flora y que a su vez aporten herramientas para su conservación.